PENGARUH KEBIASAAN SISWA MENJAWAB SOAL URAIAN TERHADAP HASIL UN 2018 - Safari, Safari (Pusat Asesmen dan Pembelajaran, 2019)
The main purpose of this study is to answer the following question Is there any influences of students' habits in answering the essay questions toward the results of the 2018 SMP National Exam (UN)? The population of this study was SMP students who participated in the 2018 UN. The data in this study is provide in the form of test scores and student answers on questionnaires taken from 34 provinces throughout Indonesia. The questionnaire was filled in voluntarily on the last day of the UN, so the number of respondents who filled out the questionnaire was 3.224.331 students from 37.859 junior high schools. These respondents is a sample in this study. Based on the results of the T-test analysis, the following results were obtained. The effect of students' habits in answering the essay questions on 2018 UN results is proven. This means that there is a significant difference (P <0,000) between students who are used to and are not used to answer essay questions on the results of the 2018 National Examination. The conclusion is that there is a significant difference between the students who are used to and not used to answer essay questions toward the results of the National Examination 2018 for subjects: Indonesian, English, Mathematics, and Natural Sciences, (Sig. 0,000).